Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Sikap Ilmiah dan Hasil Belajar Kognitif Mahasiswa pada Mata Kuliah Ekologi Tumbuhan - Hadi Purwanto; Siti Aminah; Witri Ramadhani; Fauzan Azim (Journal of Natural Science and Integration, 2020)
This study aims to determine the increase in scientific attitudes and cognitive learning outcomes of students in plant ecology courses through the application of problem-based learning models. This research was conducted on 4D grade students of the Biology Education Study Program, FKIP Riau Islamic University. This research is a classroom action research conducted in two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. Data were collected through observation sheets and cognitive learning outcomes tests. The results of data analysis in the first and second cycles showed an increase in students' scientific attitudes by 12.03% and an increase in student absorption from the first cycle to the second cycle by 5.5% and classical completeness increased by 20% from the first cycle to the second cycle. In general, it can be concluded that the application of problem-based learning models can improve scientific attitudes and cognitive learning outcomes of 4D grade students of the Biology Education Study Program, FKIP Riau Islamic University in plant ecology courses.Keywords: cognitive learning outcomes, scientific attitude, problem based learning modelABSTRAK.Penelitian ini bertujuan untuk mengetahui peningkatan sikap ilmiah dan hasil belajar kognitif mahasiswa pada mata kuliah ekologi tumbuhan melalui penerapan model pembelajaran problem based learning. Penelitian ini dilaksanakan pada mahasiswa kelas 4D Program Studi Pendidikan Biologi FKIP Universitas Islam Riau. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus, setiap siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Data dikumpulkan melalui lembar observasi dan tes hasil belajar kognitif. Hasil analisis data siklus pertama dan kedua menunjukkan adanya peningkatan sikap ilmiah mahasiswa sebesar 12,03% dan daya serap mahasiswa mengalami peningkatan dari siklus pertama ke siklus kedua sebesar 5,5% serta ketuntasan klasikal meningkat sebesar 20% dari siklus pertama ke siklus kedua. Secara umum dapat disimpulkan bahwa penerapan model pembelajaran problem based learning dapat meningkatkan sikap ilmiah dan hasil belajar kognitif mahasiswa kelas 4D Program Studi Pendidikan Biologi FKIP Universitas Islam Riau pada mata kuliah ekologi tumbuhan. Kata kunci: Hasil belajar kognitif, sikap ilmiah, model pembelajaran berbasis masalah